Sistem Monitoring Penyiraman Otomatis Tanaman Bunga Gemitir Menggunakan Aplikasi Mobile dan Web Thingspeak - I Wayan Sutama; Adie Wahyudi Oktavia Gama; I Gede Artha Negara; I Dewa Putu Arjun Suhartana Wisesa (Jurnal Ilmiah Telsinas, 2021)
The role of technology is very important in an automatic watering monitoring system that works based on the YL69 sensor and DHT11 sensor. This study aims to determine the working principle of sensors in a plant watering monitoring system with mobile applications (Blynk) and thingspeak web. Thingspeak web design aims to process data recording. To process and dispatch YL69 sensor data and DHT11 sensor, the Arduino UNO microcontroller is used as well as a relay as a switch to drain and disconnect the electric current to the water pump. The design results show that this automatic plant watering monitoring system can work well, where the soil moisture is below <50%, the water pump will live "ON" and if the soil moisture is above> 60% the water pump will die "OFF". From the results of the design and testing of the monitoring system carried out it is able to monitor data from the YL69 sensor, DHT11 sensor and pump conditions in real-time with the mobile application (Blynk). While the thingspeak web can monitor and record YL69 sensor data, DHT11 sensors and pump conditions every 20 seconds..